Financial Performance and Some Factors that Influence: An Empirical Study on Manufacturing Company - Fedra Valeria Setiawan; Agustin Ekadjaja (International Journal of Application on Economics and Business, 2023)
Financial performance is a complex matter and it cannot be separated from the efficiency of the company's activities. Regarding to the statement, the purpose of this study is to find out empirically how the influence of leverage, firm size, firm age, and cash flow on financial performance of manufacturing companies in the non-cyclical consumption sector period 2017-2020. The sample collection method used is judgement sampling with 31 manufacturing companies and 124 total observations of manufacturing companies data. This research uses EViews version 12.0 as a data processing software. This study shows results that cash flow have a positive effect on financial performance, but leverage, firm size, and firm age have no effect on financial performance.